A brass wire electric discharge machining variable optimization of aluminium–nano alumina composite. (2020) - Rajkumar, K.; Balasubramaniyan, C.; Nambiraj, K.M.; Rajesh, M.
Highlights: Aluminum-nano alumina composite was fabricated. Wire cut EDM of straight slit has been done on composite. Taguchi based design of experiments were done. Kerf and surface characteristic variation optimized with various control factor. Peak plasma discharges vaporized metal and nano alumina particle. Abstract: Aluminium metal matrix composites (AMMCs) showing an extreme abrasion action against the cutting tool is preventing usage in the multi-industrial field of aerospace, automotive and defence applications. The advent of the nano alumina reinforcement nano alumina is improving the ductile aluminium matrix strength and fracture toughness. Wire based electric discharge cutting is a quite simple and effective method for machining of MMCs. A comprehensive straight profile cutting study was performed on MMC reinforced with nano alumina particle with various controlling factors and its effect on the process characteristics. Taguchi's L18 orthogonal array-based experimentation is planned with various machining parameters on the expected outcome are estimated through ANOVA and S/N ratio scheme. These combined data analyses providing pulse on time and voltage were strongly affecting the machining characteristics. This works increasing visibility of Taguchi method to obtain the surface integrity with minimum experiments.